2022
DOI: 10.3389/fbioe.2022.811875
|View full text |Cite
|
Sign up to set email alerts
|

Application of Perinatal Derivatives in Ovarian Diseases

Abstract: Reproductive diseases could lead to infertility and have implications for overall health, most importantly due to psychological, medical and socio-economic consequences for individuals and society. Furthermore, economical losses also occur in animal husbandry. In both human and veterinary medicine, hormonal and surgical treatments, as well as assisted reproductive technologies are used to cure reproductive disorders, however they do not improve fertility. With ovarian disorders being the main reproductive path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…From this extensive work of literature search and selection and data extraction, several systematic and comprehensive reviews are published already. These publications gathered and analyzed the existing literature on the application of preclinical studies on different fields, namely cutaneous wound healing [ 5 ], ovarian diseases [ 3 ], oncology [ 6 ], and ophthalmology [ 4 ]. All of these publications used the common search and data extraction strategy described here, with additional, disease-specific refinements as described in detail in the respective publications.…”
Section: Discussionmentioning
confidence: 99%
“…From this extensive work of literature search and selection and data extraction, several systematic and comprehensive reviews are published already. These publications gathered and analyzed the existing literature on the application of preclinical studies on different fields, namely cutaneous wound healing [ 5 ], ovarian diseases [ 3 ], oncology [ 6 ], and ophthalmology [ 4 ]. All of these publications used the common search and data extraction strategy described here, with additional, disease-specific refinements as described in detail in the respective publications.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is involved in several reproductive disorders including polycystic ovary syndrome (PCOS), endometriosis, and POI [ 22 ]. POI is also characterized by decreased antioxidant levels and increased oxidative stress in cumulus cells, oocytes and ovaries, and oxidative stress levels are correlated with worse outcomes [ 23 ]. Recently, gene set enrichment analysis (GSEA) using both Hallmark and KEGG gene sets in POI patients showed that POI is associated with inhibition of pathways related to oxidative phosphorylation, DNA damage repair and mitochondrial function, such as PI3K/AKT/mTOR pathways, and early and late estrogen response pathways [ 24 ].…”
Section: Poi Pathogenesis Featuresmentioning
confidence: 99%
“…Lifestyle and environmental factors affect infertility, and great advances have gained on its diagnosis and management in recent years 2 . The ovarian disorders are the main reproductive pathologies contributing to infertility in female, including follicular atresia 3 . Granulosa cells are essential for follicular development, and dysfunctional granulosa cells are linked to follicular atresia progression 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The ovarian disorders are the main reproductive pathologies contributing to infertility in female, including follicular atresia. 3 Granulosa cells are essential for follicular development, and dysfunctional granulosa cells are linked to follicular atresia progression. 4,5 The oxidative stress is one of the causal mediators of female reproductive diseases, 6 which leads to apoptosis of granulosa cells and subsequent follicular atresia.…”
Section: Introductionmentioning
confidence: 99%